Technology of extraction and primary processing of low-grade and off-balance ores - Cheban Anton (E3S Web of Conferences, 2020)
In connection with the decline in the quality of reserves of many types of mineral wealth, there is a need to develop mining techniques and technologies that allow for effective development of deposits having increasingly hard mining conditions. In the ores of non-ferrous, rare and noble metals, the concentration of ore minerals in small classes of loosened ore mass is often observed. The paper analyzes the nature of the distribution of gold, tungsten, lead and some other useful components in the original ores, and presents methods for the treatment and primary processing of the ore mass with the separation of enriched classes. An engineering and technological solution has been proposed that provides an increase in production efficiency in opencast mining of deposits, the ores of which, after disintegration, are characterized by the enrichment of small classes, due to the separation of substandard ore siftings in the mine face directly during mining operations, their subsequent sorting and processing, as well as increased productivity and extended functionality of mining equipment. The use of the mining complex when excavating the rock mass will provide a reduction in the cost price, which will allow the complex-structured areas of the deposits to be involved in the development, composed of low-grade and off-balance ores.